Experimental Results between Non-Linear and Linear Precoding Using Multiuser MIMO Testbed - Matsumoto, Tomoko; Hatakawa, Yasuyuki; Kitagawa, Koichiro; Konishi, Satoshi (2013 IEEE 77th Vehicular Technology Conference (VTC Spring), 2013)
This paper presents the development of an 8-by-8 real-time multiuser-multiple input multiple output (MU-MIMO) testbed and experimental results of linear and non-linear precoding subject to limited channel state information (CSI) feedback. Linear precoding techniques such as minimum mean square error precoding have already been tested and the related results are available in the literature. However, they are not capacity-achieving. Non-linear precoding techniques such as vector perturbation and Tomlinson-Harashima precoding, on the other hand, achieve in theory the capacity of MU-MIMO, but such claims have not been verified in practice to date. One reason is that theoretical non-linear precoding works rely on the assumption of full and perfect CSI at the transmitter as non-linear precoding techniques are sensitive to CSI error. The merit of this work is that it experimentally confirms (through hardware implementation and pre-field test experimentation) the feasibility of non-linear precoding subject to limited CSI feedback. Experimental results reveal that the non-linear precoding achieves higher throughput performance than the linear precoding scheme by about 35% under realistic CSI feedback.